Interconnection of speed, power and speed-power abilities of professional hockey players on ice and out of ice - V.E. Zankovets; V.P. Popov (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: determination of correlation's degree between speed, power and speed-power abilities of professional hockey players on ice and out of ice. Material: 65 professional hockey players of age from 16 to 33 years old were tested. 75 highly qualified coaches were questioned. Results: The found out interconnections between 11 indicators of speed, power and speed power qualities supplement knowledge about transfer physical qualities. We detected high interconnection between speed and speed-power abilities, manifested by sportsmen in exercises on ice and on land. We registered moderate level of interconnection between static (absolute) power and speed abilities of hockey players. We proved hypothesis about possibility of start speed (power) transfer in different conditions of its manifestation. Conclusions: the received data permit to correct hockey players' training program, considering new knowledge about transfer of one or the other physical qualities on sportsmen's training.